Injustiça socioambiental nos cruzamentos da história e memória: comunidade Quilombola Nossa Senhora do Chumbo - Mendes, Giovana Rosangela Ferreira (2020)
The objective of this thesis was to investigate, to analyze and to present the many aspects relative to the socioenvironmental impacts of the sugarcane agroindustry on the ways of life of the Nossa Senhora do Chumbo quilombola community, through the perceptions of community members, and taking into account gender, class and race aspects. The community is located at the northern region of the Mato Grosso Pantanal, known as the “Cerrado do Pantanal”, located in the municipality of Poconé, in the south-central portion of the state of Mato Grosso, in the Upper Pantanal microregion. Qualitative social research procedures were used in the research, as life stories and interviews with social agents selected by their representativeness in the community in relation to their experience with sugarcane socio-environmental implications in the region. Conflicts in the region began with the implementation of the sugarcane agroindustry, with unequal disputes between residents of communities that had and have their culture, identity and territory threatened by dominant groups, especially agribusiness. In the region, the deforestation carried out for the introduction of sugarcane monoculture and livestock have motivated conflicts between the owners of these large enterprises and the social agents who live from family farming and working in the mines. From the 1980s through 2012, we realized that these agents were subject to expropriation. As in other locations, this expulsion produced migration to search for work, which made the sugarcane agroindustry in the community a destination for this workforce composed by local people and migrants from the Northeast. The social and environmental impacts resulting of the implementation of sugarcane agro-industry in the community weigh disproportionately on different groups in this territory due to social and economic vulnerability, characterizing environmental injustice.